Wind power generation - Breeze, Paul; ScienceDirect eBooks ([London] : Academic Press, an imprint of Elsevier, 2016)
Wind Power Generation is a concise, up-to-date and readable guide providing an introduction to one of the leading renewable power generation technologies. It includes detailed descriptions of on and offshore generation systems, and demystifies the relevant wind energy technology functions in practice as well as exploring the economic and environmental risk factors. Engineers, managers, policymakers and those involved in planning and delivering energy resources will find this reference a valuable guide, to help establish a reliable power supply address social and economic objectives.
Online resource; title from PDF title page (EBSCO, viewed November 5, 2015).
Includes bibliographical references.
Safari Books Online
Elsevier
Keywords: Wind power; TECHNOLOGY & ENGINEERING / Mechanical; Wind power; Electronic books